Psychotic symptoms in methamphetamine psychotic in-patients - Srisurapanont M. (2014)
The present study was aimed at exploring the prevalence and factor structure of methamphetamine (MA) psychotic symptoms. The data were obtained from a cross-country evaluation of substance use, health, and treatment in MA psychotic in-patients. The prevalence rates of lifefime and current psychotic symptoms were determined by using Mini-International Neurospychiatric Interview-Plus, Module M. The Manchester scale was used to assess the severity of psychotic symptoms during the week prior to assessment. All eight items of the Manchester scale were subjected to principal-component analysis, eigenvalue one test, and varimax rotation. The data of 168 patients (127 male and 41 female) included in the analyses were obtained from Australia, Japan, the Philippines and Thailand. Persecutory delusion was the most common lifetime psychotic symptom found in 130 participants (77.4%), followed by auditory hallucinations, strange or unusual beliefs, and thought reading. Auditory hallucinations were the most common current symptom found in 75 participants (44.6%), followed by strange or unusual beliefs and visual hallucinations. Current negative symptoms were also found in 36 patients (21.4%). Apart from a factor of anxiety and depression, the results yielded a two-factor model of MA psychotic symptoms, which were negative and positive/disorganized syndromes. The negative syndrome comprised poverty of speech, psychomotor retardation, and flattened/incongruous affects. The positive syndrome consisted of delusions, hallucinations, and incoherent speech. Both positive/disorganized and negative syndromes should be taken into account in assessing MA psychotic symptoms. The clinical findings do not support the shortcomings of amphetamine-induced psychosis in modelling the negative symptoms of schizophrenia.